2008
DOI: 10.1007/s10616-008-9145-0
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activity of chloroformic extract of Persian Shallot, Allium hirtifolium, on tumor cell lines

Abstract: Allium hirtifolim (Persian Shallot) belongs to Allium genus (Alliaceae family). We investigated the in vitro effects of chloroformic extract of A. hirtifolium and its Allicin on the proliferation of HeLa (cervical cancer), MCF7 (human, caucasion, breast, adenocarcinoma) and L929 (mouse, C3H/An, connective) cell lines. Our results showed that components of A. hirtifolium might inhibit proliferation of tumor cell lines. This inhibition in HeLa and MCF-7 cells was dose-dependent. The presence of Allicin was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…The MIC/MBCs of ASHE (32/128  μ g mL −1 ) and ASDE (64/128  μ g mL −1 ) for MRSA are comparatively lesser than the CC 50 concentrations on Vero cells (<383.4  μ g mL −1 ; <390.6  μ g mL −1 ) which is therapeutically acceptable for a nontoxic edible natural extract. Chloroformic extract of A. hirtifolium bulbs suppressed the growth of HeLa and MCR-7 cells at 200  μ g mL −1 [31], while the hydromethanolic extract of A. hirtifolium remains nontoxic to mammalian cells at 1500  μ g mL −1 [20]. These results are partly in agreement with our results, which for the first time report the in vivo antibacterial and burn wound healing activities of hexane and dichloromethane extracts prepared from the bulbs of A. stipitatum .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The MIC/MBCs of ASHE (32/128  μ g mL −1 ) and ASDE (64/128  μ g mL −1 ) for MRSA are comparatively lesser than the CC 50 concentrations on Vero cells (<383.4  μ g mL −1 ; <390.6  μ g mL −1 ) which is therapeutically acceptable for a nontoxic edible natural extract. Chloroformic extract of A. hirtifolium bulbs suppressed the growth of HeLa and MCR-7 cells at 200  μ g mL −1 [31], while the hydromethanolic extract of A. hirtifolium remains nontoxic to mammalian cells at 1500  μ g mL −1 [20]. These results are partly in agreement with our results, which for the first time report the in vivo antibacterial and burn wound healing activities of hexane and dichloromethane extracts prepared from the bulbs of A. stipitatum .…”
Section: Discussionsupporting
confidence: 90%
“…Significant amount of the presence of allicin (a major bioactive compound of Allium family) in the bulbs of A. hirtifolium Boiss. has also been demonstrated by TLC methods [31]. In contrast, only a low percentage of sulfur compounds including S-methyl methanethiosulfonate, 2,4,5-trithiahexane, 2,4-dithiapentane, 2-pyridinethione, and methane (chloromethylthio) (methylthio) were detected in the present study.…”
Section: Discussionsupporting
confidence: 44%
“…(Persian shallot) is one of the Iranian native spices [6, 13] which belong to the same biological genus of Allium sativum (garlic) and other onions [14]. It is one of the valuable members of Allium with its bulbs commonly used as a traditional remedy [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…In Iranian folk medicine, mooseer has been successfully used for treating rheumatic and inflammatory disorders. In addition, different medicinal properties such as antitrichomonas, antiproliferative, and immunomodulatory activities have also been reported for the bulbs of mooseer (Mozaffarian, 2008;Ghodrati Azadi et al, 2008;Jafarian et al, 2003;Amin, 1991). Results of previous studies (Ashrafi et al, 2004;Ismail et al, 2013) indicated that the aqueous and methanol extracts of mooseer bulbs have antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%